Impact of moving to a new hospital build, with a high proportion of single rooms, on healthcare-associated infections and outbreaks. Issue 2 (February 2018) - Darley, E.S.R.; Vasant, J.; Leeming, J.; Hammond, F.; Matthews, S.; Albur, M.; Reynolds, R.
Summary: Clostridium difficile infection, meticillin-sensitive Staphylococcus aureus (MSSA) and Escherichia coli bacteraemia rates, and bed-days lost during norovirus outbreaks at North Bristol NHS Trust were analysed over a five-year period to determine whether moving to a new-build hospital with 75% single rooms reduced healthcare-associated infection rates. C. difficile, MSSA bacteraemia and E. coli bacteraemia showed no change in the rate of decline after the move. Bed-days lost due to norovirus were significantly lower after the move. Increased availability of single rooms had an impact on the transmission of highly contagious norovirus infection, dispersed via the airborne route, in contrast to bacterial infections, which may originate from patient's own colonizing flora and are not widely dispersed through airborne spread.